Decreases of calcium and phosphorus in monkey cardiac walls with development and aging - Setsuko Tohno (2018)
To elucidate compositional changes of the cardiac walls with development and aging, the authors investigated changes of elements in the atrial and ventricular walls of monkeys. The left and right atrial walls, left and right ventricular walls, and interatrial and interventricular septa were resected from the subjects. The subjects consisted of 17 rhesus and 13 Japanese monkeys, ranging in age from 10 d to 33 yr. The element content of the cardiac walls was analyzed by inductively coupled plasma-atomic emission spectrometry. The Ca and P contents decreased in all of the left and right atrial and ventricular walls, interatrial septa, and interventricular septa with development, whereas the S and Mg contents decreased in the left and right ventricular walls with development. Regarding the relationships among elements, significant direct correlations were found among Ca, P, Mg, and Zn in all of the left and right atrial walls, left and right ventricular walls, and interatrial and interventricular septa, with some exceptions. As Ca decreased in the cardic walls, P, Mg, and Zn decreased simultaneously in the cardiac walls. The mass ratio of Ca/P decreased gradually with Ca decrease in both the atrial and ventricular walls, but it was not constant. © Copyright 2006 by Humana Press Inc. All rights of any nature, whatsoever, reserved.